If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = W + -9 Reorder the terms: -6 = -9 + W Solving -6 = -9 + W Solving for variable 'W'. Move all terms containing W to the left, all other terms to the right. Add '-1W' to each side of the equation. -6 + -1W = -9 + W + -1W Combine like terms: W + -1W = 0 -6 + -1W = -9 + 0 -6 + -1W = -9 Add '6' to each side of the equation. -6 + 6 + -1W = -9 + 6 Combine like terms: -6 + 6 = 0 0 + -1W = -9 + 6 -1W = -9 + 6 Combine like terms: -9 + 6 = -3 -1W = -3 Divide each side by '-1'. W = 3 Simplifying W = 3
| -4(3x-6)+3=-12x+27 | | y=-5t+15t+40 | | y+1=2y-10 | | 3=6+3y | | 5a^2x^2-20a^3x=0 | | 4+9y=40 | | -8x-18y=2 | | 20(x+1)=1000 | | y=14y+1 | | 10x+15y=26000 | | 5x+2y+13=0 | | -16y=128 | | 2+2q=35+q | | 10x-15y=26000 | | 6y+4=8y+3 | | U-5=.5U+14 | | 14y+1=16y+4 | | (X+6)4=120 | | 35+2x=4y | | 2x^2+8x+3x+12=1 | | 3(-6-.25y)-y=-11 | | 15p-1=5(p-1)-2(7-2p) | | 8+5y=28 | | 10(y+6)=20 | | 6p-1=5(p-1)-2(7-2p) | | 3x-5-29=90 | | 3(x-3)=2x-1 | | 4u-6=-14 | | 41-13+9w=118 | | 8d-d-9=2d | | 13=2y+5 | | 3a-12b=15 |